2002
DOI: 10.1124/dmd.30.12.1497
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nonspecific Microsomal Binding on Apparent Intrinsic Clearance, and Its Prediction from Physicochemical Properties

Abstract: ABSTRACT:The apparent intrinsic clearance of 13 drugs has been determined using rat liver microsomes at three different concentrations of microsomal protein. The kinetics was studied using the in vitro half-life method. The nonspecific binding of these drugs to the microsomes was also studied under the same conditions, except for cofactor removal, using equilibrium dialysis. The intrinsic clearances are shown to be dependent on the microsomal concentration, but are approximately constant when corrected for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
366
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(386 citation statements)
references
References 15 publications
11
366
0
Order By: Relevance
“…Some controversy also still exists over use of fu inc , with some laboratories having suggested that fu inc and fu b may cancel, negating their inclusion in liver models (Obach et al, 1997). Recent reports have challenged this assumption (Obach, 1999;Austin et al, 2002) and perhaps suggest that consideration of CL h rather than CL int, in vivo may desensitize such analyses, particularly to errors associated with higher enzyme activities (Ito and Houston, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some controversy also still exists over use of fu inc , with some laboratories having suggested that fu inc and fu b may cancel, negating their inclusion in liver models (Obach et al, 1997). Recent reports have challenged this assumption (Obach, 1999;Austin et al, 2002) and perhaps suggest that consideration of CL h rather than CL int, in vivo may desensitize such analyses, particularly to errors associated with higher enzyme activities (Ito and Houston, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some controversy also still exists over use of fu inc , with some laboratories having suggested that fu inc and fu b may cancel, negating their inclusion in liver models (Obach et al, 1997). Recent reports have challenged this assumption (Obach, 1999;Austin et al, 2002) and perhaps suggest that consideration of CL h rather than CL int, in vivo may desensitize such analyses, particularly to errors associated with higher enzyme activities (Ito and Houston, 2004).The aim of this study was to investigate direct in vitro-in vivo scaling of human in vitro data generated in hepatocytes and microsomes for predicting human clearance in vivo by applying recently described models for estimating fu inc (Austin et al, 2002(Austin et al, , 2005. To provide a more mechanistic insight, in vitro human CL int data were compiled from recent in-house and published studies, and associated in vivo CL int values were derived from published CL h data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The unbound K I (K I, u ) was calculated according to equation (6), where f u, m is the free fraction of erlotinib in the microsomes. f u, m is predicted according to equation (7) as previously reported [28] . The terms are defined as follows: C mic is the microsomal protein concentration used in the preincubation, and logP is the log of the octanol-water (pH 7.4) partition (P) coefficient of the erlotinib.…”
Section: Inactivation Constant (K I and K Inact ) Assaysmentioning
confidence: 99%
“…To determine kobs (observed inactivation rate) values, the decrease in natural logarithm of activity over time was plotted for each noscapine concentration, and kobs values were described as the negative slopes of the line. Inactivation kinetic parameters were calculated using nonlinear regression of the data according to the Equation 1: as previously reported [14]. The terms are defined as follows: Cmic is the microsomal protein concentration used in the preincubation, and LogP is the log of the octanolbuffer (pH = 7.4) partition (P) coefficient of the noscapine.…”
Section: Estimation Of Inactivation Constantsmentioning
confidence: 99%